2016
DOI: 10.1016/j.canep.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus not detected in esophageal adenocarcinoma tumor specimens

Abstract: We found no evidence of HPV DNA in esophageal adenocarcinoma tumor cells. HPV is unlikely to cause EAC or GEJAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…While the association between HPV and EC remains under discussion despite all evidences (Antonsson et al , 2016), the etiological role of BPV in EC is well established (Borzacchiello et al , 2003). EC in cattle is a self-limiting disease, being directly associated to BPV-4 infection (Borzacchiello et al , 2003; Masuda et al , 2011).…”
Section: Bpv-associated Malignant Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the association between HPV and EC remains under discussion despite all evidences (Antonsson et al , 2016), the etiological role of BPV in EC is well established (Borzacchiello et al , 2003). EC in cattle is a self-limiting disease, being directly associated to BPV-4 infection (Borzacchiello et al , 2003; Masuda et al , 2011).…”
Section: Bpv-associated Malignant Neoplasmsmentioning
confidence: 99%
“…Scarce epidemiological data about EC in cattle are available. In humans, EC has a variable incidence according to geographic area (Bjørge et al , 1997; Syrjänen, 2002; Guo et al , 2012; Nasrollahzadeh et al , 2015; Antonsson et al , 2016). Among countries with high EC incidence are China, Singapore, Iran, South Africa and Brazil (Bey et al , 1976; Han et al , 1996; Syrjänen, 2002; Guo et al , 2012).…”
Section: Bpv-associated Malignant Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings from Antonsson et al[88] showed the results of DNA quality testing (b-globin) through PCR and evaluation of the presence of HPV DNA in 241 histologically confirmed archived EAC and GEJAC (gastro-esophageal junction adenocarcinomas) tissue specimens from a population-based study in Australia. With a 97% DNA yield and acceptable quality in 233/241 specimens (201 EAC, 32 GEJAC), each sample was tested three times for HPV DNA.…”
Section: Hpv and Esophageal Cancermentioning
confidence: 99%
“…69,70 Previously published studies using PCR techniques that showed negative results were due to poor tissue classification, suboptimal testing methodology exacerbated by low viral load, old specimen samples susceptible to DNA/RNA degradation, as well as ethnic and regional variations. [71][72][73][74][75] Instead of fresh frozen material, almost all of these retrospective investigations used paraffin-embedded tissue, which yields a significant false negative HPV PCR DNA result. 68 Some studies misclassified as negative used only nondysplastic BE.…”
Section: Hpv and Adenocarcinoma Of The Esophagusmentioning
confidence: 99%